Articulation de deux approches, holiste et analytique, pour étudier le parcours professionnel de l’entrepreneur dirigeant d’entreprise - Varvara Ciobanu-Gout (Éducation et Socialisation)
Entrepreneurship is a sought-after research topic and the fields of education and skill training are no exception. However, the latest models of the entrepreneurial process agree on the complexity of this research topic. Studying the professionalisation process of the entrepreneur requires inspecting and reinventing the conventional study methods. This article presents, from a methodological angle, an investigation aiming to study the professionalisation of the business-runner entrepreneur. To understand the trends in this process, this study articulates two methodological and theoretical frameworks stemming from the biographical method: the ethnosociological investigation and the biographical approach. This multi-fold perspective allows one to study the professionalisation process in its entirety: anchored in a specific environment but also in a life path.